2000
DOI: 10.1037/h0087332
|View full text |Cite
|
Sign up to set email alerts
|

On subtypes of developmental dyslexia: Evidence from processing time and accuracy scores.

Abstract: Phonological dyslexics (Ph-DYS) are characterized by a phonological deficit, and surface dyslexics (S-DYS), by an orthographic deficit. Four issues were addressed in this study. First, we determined the proportions of Ph-DYS and S-DYS in a population of French dyslexics by applying the Castles and Coltheart's regression method (1993) to two previously unused diagnostic measures, pseudoword and irregular-word processing time. Thirty-one dyslexics were matched to 19 same-age average readers (10-years-old, CA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
133
3
16

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 54 publications
13
133
3
16
Order By: Relevance
“…In addition, the length of pseudowords was manipulated, because some apparently inconsistent results on the length effect have been found, even in English (Rack et al, 1992;Van Ijzendoorn & Bus, 1994). Finally, compared to the sample of a previous French study (Sprenger-Charolles et al, 2000), the dyslexics included in the present study were younger and more severely impaired, so that the trends observed in the previous study were expected to be replicated and reinforced. Especially, differences between dyslexics and RL controls were expected to be observed even in regard to accuracy scores, as in studies conducted with English-speaking dyslexics.…”
Section: Results Of Group Studiesmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, the length of pseudowords was manipulated, because some apparently inconsistent results on the length effect have been found, even in English (Rack et al, 1992;Van Ijzendoorn & Bus, 1994). Finally, compared to the sample of a previous French study (Sprenger-Charolles et al, 2000), the dyslexics included in the present study were younger and more severely impaired, so that the trends observed in the previous study were expected to be replicated and reinforced. Especially, differences between dyslexics and RL controls were expected to be observed even in regard to accuracy scores, as in studies conducted with English-speaking dyslexics.…”
Section: Results Of Group Studiesmentioning
confidence: 86%
“…Because of ceiling effects on irregular-word accuracy in CA controls, the regression method was used only for correct-response latencies in one study (Sprenger-Charolles et al, 2000). In sharp contrast with the results obtained with the classical method, the regression method pointed out a high percentage of soft-dissociated profiles, and a low percentage of mixed profiles.…”
Section: Results Of Multiple-case Studiesmentioning
confidence: 94%
See 3 more Smart Citations